Application of ultrasound‐guided percutaneous intrahepatic portal vein catheterization with antibiotic injection for treating unliquefied bacterial liver abscess. Issue 3 (26th July 2016) - Xu, Shihao; Wang, Yiluan; Chen, Jingfeng; Hu, Yuanping; Zhang, Qiyu; Chen, Gang; Yu, Fuxiang
Abstract : Aim: To investigate whether ultrasound‐guided percutaneous portal vein catheterization can be successfully carried out in the intrahepatic region of patients with unliquefied bacterial liver abscess (UBLA), who are subsequently treated with an injection of antibiotics. Methods: Thirty‐two UBLA patients were enrolled in this study. Among them, 13 patients were included in the experimental group; an ultrasound‐guided percutaneous portal vein catheterization was undertaken in the intrahepatic region of these patients, and they also received an injection of antibiotics. The remaining 19 patients were retrospectively included in the control group; these patients only received systemic antibiotic therapy. The efficacy of intervention was compared with that of systemic treatment. Results: The catheterization procedures were successful in all the patients of the experimental group. However, two cases (15.4%) developed complications postoperatively. Compared to the control group, the following parameters of the experimental group were significantly shorter/lower: (i) duration for regaining normal body temperature; (ii) time period for achieving normal white blood cell count; (iii) length of hospitalization; (iv) cases of liquefied liver abscess during follow‐up; and (v) cost of hospitalization ( P < 0.05). Conclusion: Ultrasound‐guided percutaneous portal vein catheterization is a simple, minimally invasive, and effective treatment for UBLA. It must be carried out in the intrahepatic region and a subsequent injection of antibiotics must be given.